Lawyer nation : the past, present, and future of the American legal profession - Brescia, Ray (New York : New York University Press, 2024)
"At this time of tumultuous change and threats to the rule of law in the United States, Lawyer Nation explores the critical role that American lawyers have played since the nation's founding, and the role they must play today and in the future, in defending and advancing justice and inclusion in our multi-racial democracy"--
A janus-faced profession -- An index to the character of the people -- An independent bar and an honest judiciary -- The profession in crisis and the institutional response -- The legal profession as an institution -- A public health crisis and the institutions of exclusion -- A serpent in the ear of the president -- The access-to-justice crisis and the rise of legal technology -- The purpose of the profession.
Includes bibliographical references (pages 245-283) and index.
Print version record.
JSTOR
Keywords: Practice of law -- United States; Lawyers -- United States; Droit -- Pratique -- États-Unis.; Avocats -- États-Unis.; LAW / Legal Profession; Lawyers; Practice of law; United States